The Use of Mediation to Resolve Community Disputes - Charles B. Craver (Washington University Journal of Law & Policy, 2015)
Craver calls for a greater recognition that mediation as a form of dispute resolution is essentially akin to assisted negotiation, and argues that this form of dispute settlement should be utilized more frequently in disputes among members of a community. Craver suggests that successful mediation can help assuage community members of the typical negative social pressure associated with inter-community litigation, and provides that such mediation can enhance the psychological well-being of the negotiating parties. This Article explores the best practices for mediators that are engaged in resolving community disputes.
Keywords: dispute resolution; mediation; community disputes; assisted negotiation